Recovery from visuospatial neglect in stroke patients. Issue 4 (1st April 1998) - Cassidy, Timothy P; Lewis, Susan; Gray, Christopher S
Abstract : OBJECTIVES: To describe the natural recovery of visuospatial neglect in stroke patients and the distribution of errors made on cancellation tests using a standardised neuropsychological test battery. METHOD: A prospective study of acute (< seven days) patients with right hemispheric stroke. Patients identified with visuospatial neglect were followed up for three months with monthly clinical and neuropsychological testing RESULTS: There were 66 patients with acute right hemispheric stroke assessed of whom 27 (40.9%) had evidence of visuospatial neglect. Patients with neglect, on admission, had a mean behavioural inattention test (BIT) score of 56.3, range 10–126 (normal>129). Three of the subtests identified errors being made in both the right and left hemispaces. During follow up, recovery occurred across both hemispaces, maximal in the right hemispace. Recovery from visuospatial neglect was associated with improvement in function as assessed by the Barthel score. At the end of the study period only six (31.5%) patients had persisting evidence of neglect. On admission the best predictor of recovery of visuospatial neglect was the line cancellation test (Spearman's rank correlation r =−0.4217, p=0.028). CONCLUSION: The demonstration of errors in both hemispaces has implications for the theory that neglect is a lateralised attentional problem and is important to recognise in planning the rehabilitation of stroke patients.